Die Methode von Prof. Tibor Szele im Unterricht begabter Schüler - Kántor, Sándor (Teaching Mathematics and Computer Science, 2006)
Prof. Tibor Szele' has attempted to develop the mathematical problemsolving, creativity include the use of investigations and host of other devices beyond the classroom, i.e. in "mathematical circles" for talented students in secondary schools. This paper of the author – who himself has taken part in Seles1s mathematical circles – quotes from these activities according his earlier notes. This description illustrates the didactic method of Prof. T. Szele.